STRATEGI DAN IMPLEMENTASI DALAM TATA PEMERINTAHAN DENGAN BERBASIS PENGEMBANGAN KONSEP SMART CITY - Adie Dwiyanto Nurlukman; Abdul Basit (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2021)
The development of information technology encourages the development of the Smart City model in various major cities in Indonesia. The city of Tangerang is trying to develop the Smart City through various programs that are starting to be developed by the Tangerang City Government. The Smart City concept promoted by the City of Tangerang is Tangerang LIVE. This concept has been launched since December 2013 and was implemented in 2014. This study aims to determine how the City Government realizes the concept of Smart City in Tangerang City and the obstacles that arise in it. implementation of programs from the Smart City Concept in Tangerang City. This research was conducted using a qualitative method with a focus on the Tangerang City Information and Communication Office as the main data source. The results showed that the strategy and implementation carried out by the Office of Communication and Information Technology was implemented based on Perwal no. 2 of 2016 which is guided by the RPJMD which has been compiled to support the concept of Smart City which is wrapped through Tangerang LIVE, but in the implementation of this Smart City it cannot be said to be optimal due to the lack of socialization carried out by the Communication and Informatics Office and the lack of awareness and readiness of SKPD and community to run programs from the Smart City so that it can hinder the implementation process of the Smart City